brazil@digitaldivide.com: Confronting Inequality in the Information Society - Sorj, Bernardo (SciELO Books - Centro Edelstein, 2008)
The topic of this book, the digital divide, refers to the unequal distribution of resources associated with information and communication technology between countries and within societies. We will explore how one factor, in this case information technology, can potentially support contradictory tendencies: towards greater freedom and social participation and to deeper social inequality and new forms of concentration of power (excerpt taken from the book's Introduction).